Optimasi Lokasi Staging Area pada Sistem Auto Inbound Berbasis Automated Guided Vehicle (AGV) Menggunakan Analisis Load Distance dan Cycle Time - Aditia Prajna Prasetia; Asep Hermawan; Dedy Setyo Oetomo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The development of warehouse automation systems has encouraged the implementation of Automated Guided Vehicles (AGVs) to improve material handling efficiency. However, an inappropriate staging area location may increase material movement distance and operational cycle time in the auto inbound system. This study aims to determine the optimal staging area location in an AGV-based auto inbound system using Load Distance and Cycle Time analysis. The research was conducted at the RMPM warehouse of PT Sanghiang Perkasa by evaluating several staging area alternatives based on material movement distance and AGV operational time parameters. The results show that STG 1 is the optimal location with a cycle time value of 176.274 seconds/cycle, lower than STG 2 at 228.708 seconds/cycle and STG 3 at 295.344 seconds/cycle. The optimization of staging area location can improve the operational efficiency of the auto inbound system.